Complete dynamic model of the Twin Rotor MIMO System (TRMS) with experimental validation. (September 2017) - Tastemirov, Azamat; Lecchini-Visintini, Andrea; Morales-Viviescas, Rafael M.
Abstract: In this paper we develop a complete dynamic model of the Twin Rotor MIMO System (TRMS) using the Euler–Lagrange method. Our model improves upon the model provided by the manufacturer in the user manual and upon previous models of the TRMS which can be found in the literature. The complete procedure for the model parameters' estimation and validation is illustrated.